Efeitos da divulgação Ambiental, Social e de Governança (ESG) e do conselho de administração na assimetria de informação de empresas da América Latina - Monteiro, Adriano Silva (2024)
This research aims to analyze the effects of environmental, social and governance (ESG) disclosure and the board of directors on the information asymmetry of Latin American companies (Argentina, Brazil, Chile, Mexico and Peru) from 2016 to 2022. The research is classified as quantitative in terms of its approach to the problem, descriptive in terms of its objectives and documentary in terms of its technical procedures (data collection). The data was obtained from the Refinitiv Eikon® database. Data analysis was performed for a total of 222 companies (sample), based on OLS (Ordinary Least Squares) regression with robust standard errors (with White correction). The results showed that both ESG, environmental, social and corporate governance disclosure, as well as the characteristics of the board of directors (size and independence of the board of directors (CA)) contribute to minimizing the information asymmetry of companies in Latin American countries analyzed. These results indicate that greater ESG, environmental, social and governance disclosures, as well as a smaller and inde-pendent CA reduce information opacity and agency conflicts. Furthermore, these results demonstrate to investors and interested parties that the company values transparency and that the interests of agents and principals are aligned. The findings of this research help companies, managers and CAs to understand the peculiarities of having a leaner and more independent CA, which monitors and communicates effectively, in addition to the importance of ESG disclosures, demonstrating greater business transparency, meeting this the interests of investors and other interested parties. In this way, it is hoped that the results will contribute to management, demon-strating that engaging in ESG practices should be considered a strategic decision, since ESG disclosure can improve the information environment of companies. In practical terms, the dis-closure of ESG reports provides shareholders with information on environmental, social and governance issues, filling in the gaps left by financial statements. These are aspects that inves-tors are increasingly looking at when making investment decisions. In the social sphere, the results of this research can help society by making organizations aware of the importance of disclosing ESG issues, highlighting their impacts on management, the environment and society.